父权审美观的沉溺与背离： 潘雨桐与商晚筠小说的女体书写: Women’s Body Writing in Pan Yutong and Shang Wanyun’s Short Stories - Ying Xuan, Chin (ERUDITE: Journal of Chinese Studies and Education, 2022)
潘雨桐与商晚筠可谓马华文坛中较早表现出女性关怀意识的两位小说家。无论从创作主力、表现手法、得奖经验、留学经历，甚至是生活时空来看，他们都有许多相似处。而生理性别差异则是他们最显而易见的差别。先天上的生理差异会否影响作家认知并以不同方式来书写女性人物？对此问题，女性主义者至今仍旧存有论述分歧。虽然性别议题向来是女性主义论述关注的对象，但它其实是父权体制的产物。生活于父权体制中，潘雨桐与商晚筠或多或少都会受到父权思想影响。因此本文选择以父权体制的审美观为标杆，来分析他们笔下的女性人物身体书写。企图在此标杆底下窥探男作家与女作家书写女体的异曲或同工，并提出本文对生理性别与女性人物书写之关系的看法。 Pan Yutong and Shang Wanyun are the Mahua writers who concern about women’s issue. They have a lot of similar experiences, but they are sexually different. Will this obvious distinction affected the way they describe women characters? Feminist theory are still argued on this issue. Although gender issue has always been the subject of feminists, but it is a product of patriarchy. Pan Yutong and Shang Wanyun who live in the patriarchy society may been affected by the patriarchy ideology. Therefore, this study will compare the method they describe women’s body, try to find out the similarity or differences between male and female writer. Finally, this study will also try to respond on the argument regarding this issue. Keywords: Mahua Fiction, Women’s body writing, Patriarchy, Pan Yutong, Shang Wanyun